Comparison of the Application of Vibrating Mesh Nebulizer and Jet Nebulizer in Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta‐analysis - Feng Z; Han Z; Wang Y; Guo H; Liu J (International Journal of COPD, 2024)
Zhouzhou Feng,1 Zhengcai Han,1 Yaqin Wang,1 Hong Guo,1 Jian Liu1,2 1The First Clinical Medical College of Lanzhou University, Lanzhou City, People’s Republic of China; 2Gansu Maternal and Child Health Hospital/Gansu Central Hospital, Lanzhou City, People’s Republic of ChinaCorrespondence: Jian Liu, Department of Clinical Medicine, the First Clinical Medical College of Lanzhou University, No. 1, Donggang West Road, Chengguan District, Lanzhou City, Gansu Province, People’s Republic of China, Tel +86 136 0935 4197, Email medecinliu@sina.comObjective: To comparison of the application of Vibrating Mesh Nebulizer and Jet Nebulizer in chronic obstructive pulmonary disease (COPD).Research Methods: This systematic review and meta-analysis was conducted following the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) statements. The primary outcome measures analyzed included: The amount of inhaler in the urine sample at 30 minutes after inhalation therapy (USAL0.5), The total amount of inhaler in urine sample within 24 hours (USAL24), Aerosol emitted, Forced expiratory volume in 1 second (FEV1), Forced vital capacity (FVC).Results: Ten studies were included with a total of 314 study participants, including 157 subjects in the VMN group and 157 subjects in the JN group. The data analysis results of USAL0.5, MD (1.88 [95% CI, 0.95 to 2.81], P = 0.000), showed a statistically significant difference. USAL24, MD (1.61 [95% CI, 1.14 to 2.09], P = 0.000), showed a statistically significant difference. The results of aerosol emitted showed a statistically significant difference in MD (3.44 [95% CI, 2.84 to 4.04], P = 0.000). The results of FEV1 showed MD (0.05 [95% CI, − 0.24 to 0.35], P=0.716), the results were not statistically significant. The results of FVC showed MD (0.11 [95% CI, − 0.18 to 0.41], P=0.459), the results were not statistically significant. It suggests that VMN is better than JN and provides higher aerosols, but there is no difference in improving lung function between them.Conclusion: VMN is significantly better than JN in terms of drug delivery and utilization in the treatment of patients with COPD. However, in the future use of nebulizers, it is important to select a matching nebulizer based on a combination of factors such as mechanism of action of the nebulizer, disease type and comorbidities, ventilation strategies and modes, drug formulations, as well as cost-effectiveness, in order to achieve the ideal treatment of COPD.Keywords: chronic obstructive pulmonary disease, aerosol, vibrating mesh nebulizers, jet nebulizers, meta-analysis